Secondary Schools’ role In Protecting Students From Drug Dangers and Spreading Environmental and Health Awareness Among them - Abbas Fadhil Kadhim, Lect. Dr. (lark, 2022)
The study aims to find out the role of secondary schools in protecting their students from the dangers of narcotic drugs and to spread environmental and health awareness among them from the point of view of science teachers in Al Aziziya District. The researcher uses a descriptive approach and the Statistical Package for the Social Sciences (SPSS) to achieve the objectives of the study. The study has found that secondary schools have a role concerning the subject matter of the study. Gender and other social variables have an effect on male and female teachers’ interaction with the subject matter at issue. The intermediate and preparatory academic levels of study do not affect the teachers’ interaction with the role of secondary schools. In light of the results of the study, the researcher recommends the following: Activating the role of secondary schools in protecting their students from the dangers of drugs and spreading environmental and health awareness among students from the point of view of science teachers, cooperation between the educational institution and parents on one hand and the and civil society institutions on the other, activating the role of media institutions and religious institutions, conducting more research and studies on the dangers of drugs and their negative effects.